The Evolution of Double Pylorus Associated With NSAIDs-Induced Gastric Ulcer - Sihombing, Rasco Sandy; Agustinus, Taolin; Syam, Ari Fahrial (The Indonesian Society for Digestive Endoscopy, 2025)
Double pylorus is an uncommon condition where two communicating channels between the gastric antrum and duodenal bulb exist and found incidentally by esophagogastroduodenoscopy. This case report presented a 77-year old Timorese man with long-term frequent use of nonsteroidal anti-inflammatory drugs (NSAIDs) who came to hospital because of hematemesis and melena. The initial endoscopy showed gastric ulcer and the double pylorus. Nine months later, the double pylorus structure fused into one large opening. This elderly patient with a history of NSAIDs abuse was diagnosed with acquired double pylorus due to a gastric ulcer complication. The fusion of the two channels occurred as a result of septum destruction, likely caused by fistulous tract ulceration or mechanical damage from food bolus. This structure predisposes the patient to bile regurgitation and ulcer recurrence, emphasizing the need for continued monitoring and avoidance of ulcerogenic factors. Keywords : double pylorus, gastroduodenal fistula, NSAIDs, gastric ulcer, follow-up